Identification of microplastic content in several types of Shelfish in Tanjung Batu waters, Berau regency - Kedang, Arni Sovia Sabu; Masitah, Masitah; Jailani, Jailani; Kurniawati, Zenia Lutfi; Nasution, Ruqoyyah; Rosrinda, Eadvin (Generasi Biologi Indonesia, 2022)
This study aims to determine the microplastic content in several types of shellfish in Tanjung Batu waters, Berau Regency. The type of research used is qualitative research, with descriptive analysis methods. The samples used in this study were blood clams (Anadara granosa) and cockles (Polymesoda erosa) taken from the sea waters of Tanjung Batu, Berau Regency, East Kalimantan. Observations were made at the Biology Education Laboratory, Teaching and Education Faculty, Mulawarman University. The results showed that blood clams (Anadara granosa) and cockles (Polymesoda erosa) contained microplastics. The types of microplastics found included fibers, fragments, and films. The type of microplastic that is found the most is fiber and the least is film.